Deus morto no Pampa : a religiosidade gaúcha no mito fundador proposto por Erico Verissimo - Silva, Nivaldo Pereira da (My University, 2014)
This study was based on a literary work so as to raise considerations about peculiar aspects of the culture of the state of Rio Grande do Sul in relation to Brazil. From reading on the historical novel O Continente, written by Erico Verissimo, arises the work hypothesis that religion had a different role in the development of this specific Brazilian province. It has reflections on the structure of the values that characterize this society, with emphasis on free will and political action. This research aims at giving not a present religious outline of the province, but a qualitative panorama of how such thin religiosity influenced the construction of a gaucho ethos and how much this mythic view has made it distinguished from the Brazilian ethos. The research, which has interdisciplinary character, is supported by the data and theories of Anthropology, History, Sociology, Philosophy and Psychology, besides the Christian theology.
Este estudo toma como base uma obra literária para levantar considerações sobre aspectos característicos da cultura do Rio Grande do Sul em relação ao Brasil. A partir da leitura do romance histórico O Continente, de Erico Verissimo, surge a hipótese de trabalho de que a religião teve um papel diferenciado na formação dessa peculiar região brasileira. Isso repercute na estrutura de valores que caracteriza a sociedade gaúcha, destacando o livrearbítrio e a ação política. Busca-se estabelecer não um perfil religioso atual do Estado, mas um panorama qualitativo do quanto uma fraca religiosidade influenciou na construção de um etos gaúcho e do quanto este se diferencia do etos brasileiro pelo viés mítico. A pesquisa tem caráter interdisciplinar e está apoiada em dados e teorias da antropologia, da história, da sociologia, da filosofia e da psicologia, além da teologia cristã.
Keywords: Antropologia; Religião e formação social; Mito fundador gaúcho; Mito gaúcho e história; Religion and social formation; Gaucho founder myth; Gaucho myth and History; Érico Verissimo; Literatura sul-rio-grandense; Religiosidade - Rio Grande do Sul